Some aspects of convective clouds around Delhi (MAUSAM, 1990)
Growth and decay rates as well as the durations of convective clouds in the Delhi region have studied using radar observations of such clouds, made during the pre-monsoon and monsoon seasons of 1980 to 1982. Vertical growth rates of radar echoes from such clouds varied between 1.0 and 25. 0 m/sec during pre-monsoon and between 0.9 and 12.8 m/sec during the monsoon season. Decay rates of the echoes are found to vary between 0.6 and 10.4 m/sec, and between 0.9 and 15.3 m/sec in these two seasons respectively. No significant difference was found between the average durations of the echoes in the pre-monsoon and monsoon seasons (39 and 36 minutes respectively). The mechanisms of precipitation initiation involved in these clouds have also been investigated and discussed in the paper.